Modelling the mediterranean pelagic ecosystem using the POSEIDON ecological model. Part II: Biological dynamics. (January 2020) - Kalaroni, S.; Tsiaras, K.; Petihakis, G.; Economou-Amilli, A.; Triantafyllou, G.
Abstract: A three-dimensional coupled hydrodynamic/biogeochemical numerical model, currently in operation as part of the POSEIDON forecasting system, was implemented in the Mediterranean Sea. The model was assessed regarding its efficacy in representing the main biogeochemical components and seasonal dynamics of the Mediterranean planktonic system. Model outputs were compared with available historical data in a proposed objective eco-regionalisation of the Mediterranean basin, based on productivity. The simulated production (primary, bacterial) and planktonic biomass (phytoplankton, zooplankton and bacteria), as well as particulate and dissolved organic carbon, were found consistent with observational estimates in different areas of the Mediterranean Sea, following large scale productivity gradients. Although some limitations of the model were identified, the observed variability of the phytoplanktonic community structure was reasonably well-reproduced, simulating a dominant microbial food web with an intermittent development of the classical food web. The generic POSEIDON ecosystem model skill assessment provides a benchmark for future model improvement, highlighting the need to expand the range of biological variables sampled for further model calibration and validation.